CENTRE OF ISOTOPIC AND GEOCHEMICAL RESEARCH (IGC SB RAS): CURRENT STATE OF MICRO- AND MACROANALYSIS - S. Yu. Skuzovatov; O. Yu. Belozerova; I. E. Vasil’eva; O. V. Zarubina; E. V. Kaneva; Yu. V. Sokolnikova; V. M. Chubarov; E. V. Shabanova (Геодинамика и тектонофизика)
Centre of Isotopic and Geochemical Research based on the Analytical Department of Vinogradov Institute of Geochemistry SB RAS (Irkutsk) performs a wide range of analytical studies to solve mineralogical and petrological, geochemical, prospecting, ecological, paleoclimatic and applied problems. The studies are supported by the modern equipment for electron microprobe, X-ray diffraction, X-ray fluorescence, atomic emission and mass spectrometric (including isotope) analyses, as well as the necessary international certified reference materials (SRM) and a collection of SRM of the natural and technogenic composition of our production.